Peran Orang Tua dalam Membantu Pembelajaran Daring di SDN 030 Kota Bangun - Kurnia, Mita; Musfiroh, Imroh Atul (Borneo Journal of Islamic Education, 2021)
Abstract The work background of parents who are mostly farmers and palm oil workers makes it difficult for them to divide their time between work and guiding their children, plus parents who do not really understand with children's material making parents overwhelmed in helping online learning The purpose of this study is to find out the extent of the role of parents in helping online learning at SDN 030 Kota Bangun, and the factors that influence the role of parents in helping online learning at SDN 030 Kota Bangun. The method used is descriptive qualitative. The data sources are parents of students whose children have difficulties in online learning, student representatives, parents and school principals. Collecting data through interviews, observation and documentation. The validity of the data uses triangulation of data sources, and data analysis techniques consist of data condensation, data presentation and conclusion drawing. The results of this study indicate that after the data analysis, it turns out that the role of parents in helping online learning at SDN 030 Kota Bangun there are 6 roles of parents which include 1.) the role of parents as companions, namely trying to help solve problems or learning difficulties. 2.) Establish communication by positioning as friends, 3.) supervisor, namely reminding, 4.) motivator, namely providing encouragement, 5.) directing, namely building children's awareness and 6.) as facilitator, namely providing a comfortable atmosphere and providing media or other learning support . The influencing factors are awareness and understanding of children's development, time availability, cooperation and clear boundaries for children. Kata Kunci: Role, Parent, Online Learning Abstrak Latar belakang pekerjaan orang tua yang sebagian besarnya adalah petani dan buruh sawit membuat mereka kesulitan dalam membagi waktu antara pekerjaan dan membimbing anaknya, ditambah lagi dengan orang tua yang kurang begitu paham dengan materi anak membuat orang tua kewalahan dalam membantu pembelajaran daring. Tujuan penelitian ini yaitu untuk mengetahui sejauh mana peran orang tua dalam membantu pembelajaran daring di SDN 030 Kota Bangun, dan faktor-faktor yang mempengaruhi peran orang tua dalam membantu pembelajaran daring di SDN 030 Kota Bangun. Metode yang digunakan adalah kualitatif deskriptif. Sumber datanya adalah orang tua murid yang anaknya memiliki kendala dalam pembelajaran daring, perwakilan murid, wali murid serta kepala sekolah. Pengumpulan data melalui wawancara, observasi dan dokumentasi. Keabsahan datanya menggunakan triangulasi sumber data, dan teknik analisis data terdiri dari kondensasi data, penyajian data dan pengambilan kesimpulan. Hasil penelitian ini menunjukkan bahwa setelah dilakukannya analisis data ternyata peran orang tua dalam membantu pembelajaran masa daring di SDN 030 Kota Bangun terdapat 6 peran orang tua yang meliputi 1.) peran orang tua sebagai pendamping yakni berusaha membantu memecahkan masalah atau kesulitan belajar. 2.) Menjalin komunikasi dengan memposisikan sebagai sahabat, 3.) pengawas yakni mengingatkan, 4.) motivator yakni memberikan semangat, 5.) pengarah yaitu membangun kesadaran anak Dan 6.) sebagai fasilitator yaitu memberikan suasana nyaman dan menyediakan media ataupun pendukung pembelajaran lainnya. Adapun faktor-faktor yang mempengaruhi yakni kesadaran dan pemahaman terhadap perkembangan anak, kesedian waktu, kerja sama dan batasan-batasan yang jelas bagi anak. Kata Kunci: Peran, Orang Tua, Pembelajaran Daring